Mechanical characteristics and ballistic behaviors of high strength and hardness armor steels. (October 2022) - Cheng, Y.H.; Wu, H.; Zhao, R.G.; Zhou, F.
Abstract: Armor steel has huge prospective applications in the design of military equipment against the high-speed impact of projectiles due to its high strength, hardness, ductility, etc. This study aims to assess the mechanical characteristics and ballistic behaviors of newly developed NP450 and NP510 armor steels with high strength and hardness based on systematic test and numerical simulations. Firstly, a series of basic mechanical tests, i.e., quasi-static tensile test under room (25 °C) and elevated temperatures (100-900 °C), quasi-static notched specimen tensile test (notched radii with 3 mm, 6 mm, and 9 mm), high-speed tensile test (strain rates of 10-600 s -1 ), and Split Hopkinson Pressure Bar compressive test (strain rates of 300-1900 s -1 ) were carried out. Secondly, all the parameters in the Johnson-Cook flow and fracture model for the present two armor steels were calibrated. By further conducting the Taylor impact test and the corresponding numerical simulations, these model parameters were validated by comparisons of the residual length, residual maximum diameter, and failure mode of impact specimens. Thirdly, total fifteen shots of deformable projectile (15 mm in diameter) perforation test with utilizing high-speed three-dimension digital image correlation technology was conducted to examine the ballistic behaviors of two armor steels. The effects of projectile impact velocity and target thickness on the damage modes, e.g., shear plugging, ductile tearing, ductile hole enlargement, were analyzed. The corresponding numerical simulations with the validated model parameters were performed, and the predicted residual velocity of projectile and out-of-plane displacement of target agree well with the test data. Highlights: Static and dynamic mechanical characteristics of two armor steels were studied. All J-C model parameters were calibrated and validated by Taylor impact test. Ballistic behaviors of armor steel were examined by projectile perforation test. Out-of-plane displacement of target was recorded by the high-speed 3D-DIC system. Reliability of model parameters and finite element analysis approach was verified.